An experimental setup to verify stokes’ law using an electronic balance - Dolz, M.; Casanovas, A.; Delegido, J.; Hernández, M.J. (Revista Mexicana de Física E, 2004)
An experimental setup has been designed to allow direct measurement of the force acting upon a sphere immersed in a moving fluid. This experiment confirms the direct proportionality between the force and each of the variables involved (sphere-fluid relative velocity, sphere radius and fluid viscosity). A simple experimental demonstration has been made of Stokes’ law for spheres immersed in fluids moving, for very small Reynolds numbers, along cylindrical tubes.